2014
DOI: 10.2149/tmh.2013-24
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in the Growing Incidence of Dengue Fever in Vietnam Explained by Weather Variability

Abstract: Dengue fever is a major health problem in Vietnam, but its incidence differs from province to province. To understand this at the local level, we assessed the effect of four weather components (humidity, rainfall, temperature and sunshine) on the number of dengue cases in nine provinces of Vietnam. Monthly data from 1999 to 2009 were analysed by time-series regression using negative binomial models. A test for heterogeneity was applied to assess the weather-dengue association in the provinces. Those associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 30 publications
5
39
0
1
Order By: Relevance
“…Previous studies conducted in Asia and Latin America have revealed the importance of climate conditions in dengue transmission [5457]. In this study, we found that weekly minimum temperature has a significant bimodal positive effect on dengue transmission when the value is either higher than 23°C or lower than 17°C, and the effects can last for 10–15 weeks.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies conducted in Asia and Latin America have revealed the importance of climate conditions in dengue transmission [5457]. In this study, we found that weekly minimum temperature has a significant bimodal positive effect on dengue transmission when the value is either higher than 23°C or lower than 17°C, and the effects can last for 10–15 weeks.…”
Section: Discussionsupporting
confidence: 57%
“…The entomological component of this study spans one year, which does not allow for the examination of longer term trends. Nonetheless, our findings with regards to the importance of relative humidity are consistent with time-series analyses for the region[7, 16]. Our use of dengue hospitalization rates no doubt represents only a small portion of dengue infections.…”
Section: Discussionsupporting
confidence: 86%
“…We postulate that temperature in the Mekong Delta is largely within optimum range for vector breeding and viral dissemination throughout the year. A time-series analysis on regional differences in dengue incidence in Vietnam demonstrated that in Ho Chi Minh City (near Can Tho) where annual average temperature is 28°C, dengue incidence was positively associated with relative humidity, but negatively associated with temperature [16]. This stood in contrast to Hanoi (annual average temperature of 23.6°C), where the opposite was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there appears to be a connection between the regional rainfall regime, its susceptibility to alteration under certain types of ENSO event and the pattern of provincial dengue/DHF incidence in terms of timing and possibly also intensity. This result supports findings by Vu et al () in Vietnam, where the authors observed considerable provincial variations in weather‐dengue associations leading them to recommend local rather than national‐level prevention strategies. It also supports the proposal by Hales et al .…”
Section: Discussionmentioning
confidence: 99%